THE IMPORTANCE OF USING LAPAROSCOPIC DEVICES IN PEDIATRIC SURGERY - Ayisha Milna; Gоyibnazarov Rozimurod Bakhtiyarovich; Abdullaeva Nigora Ulugbek qizi (Western European Studies, 2025)
This paper examines on laparoscopic devices in pediatric surgery
Keywords: Laparoscopic; surgery; pediatrics